Phylogenetic classification of natural product biosynthetic gene clusters based on regulatory mechanisms - Rodriguez-Sanchez, Alberto C.; Gónzalez-Salazar, Luz A.; Rodriguez-Orduña, Lorena; Cumsille, Ándres; Undabarrena, Agustina; Camara, Beatriz; Sélem-Mojica, Nelly; Licona-Cassani, Cuauhtemoc (Frontiers in Microbiology, 2023)
The Natural Products (NPs) Biosynthetic Gene Clusters (BGCs) represent the adapting biochemical toolkit for microorganisms to thrive different microenvironments. Despite their high diversity, particularly at the genomic level, detecting them in a shake-flask is challenging and remains the primary obstacle limiting our access to valuable chemicals. Studying the molecular mechanisms that regulate BGC expression is crucial to design of artificial conditions that derive on their expression. Here, we propose a phylogenetic analysis of regulatory elements linked to biosynthesis gene clusters, to classify BGCs to regulatory mechanisms based on protein domain information. We utilized Hidden Markov Models from the Pfam database to retrieve regulatory elements, such as histidine kinases and transcription factors, from BGCs in the MIBiG database, focusing on actinobacterial strains from three distinct environments: oligotrophic basins, rainforests, and marine environments. Despite the environmental variations, our isolated microorganisms share similar regulatory mechanisms, suggesting the potential to activate new BGCs using activators known to affect previously characterized BGCs.2 This is a provisional file, not the final typeset article Importance: Our study represents the first approach that classifies Biosynthetic Gene Clusters according to a regulatory structure. Through the study of known activators of well-characterized BGCs, we have identified common patterns in regulatory mechanisms, offering potential activators for previously unexplored BGCs. This research contributes to NP discovery by presenting a framework for identifying potential activators for novel BGCs, opening the door to the discovery of new Natural Products.